Institutional Arrangements for Nutrition in India : An Assessment of Capacity - Kathuria, Ashi Kohli (World Bank, Washington, DC, 2014)
The report consists of the following seven chapters. The present chapter provides the context and the rationale for the study, and outlines the methodology. Chapter two describes the nutrition system in detail and discusses the capacity issues related to the division of labor (DoL) between the two primary programs of the nutrition system and within the Integrated Child Development Services, or ICDS. Chapter three delves into the factors that constrain leadership capacity at all levels chapter four discusses the key capacity constraints related to HR that limit the effective delivery of nutrition services. Chapter five discusses the training system as a sub-system of HR and its capacity constraints, and Chapter six covers the capacity assessment pertaining to monitoring, evaluation and management of information in the nutrition system. Chapter seven discusses the capacity constraints related to General Management Practices, or GMPs in the ICDS, especially focusing on supervision, accountability and work practices and procedures.